Pengaruh Pengawasan Terhadap Kinerja Pegawai pada Badan Perencanaan Pembangunan Daerah Kabupaten Pelalawan - Ladoma, Janni Wardi; Putra, Eka (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2024)
The purpose of this study was to determine the effect of supervision on employee performance at the Pelalawan Regency Manpower Office. To achieve this goal, a study was conducted using a sample of 35 people, using the census method. Methods of data analysis using simple linear regression. Based on the test results on the control variable (X), the t-count is greater than the t-table (4.149 > 2.035). R. Square (R2) of 0.343 (34.3%) explains that the supervision variable contributes to the performance of employees of the Pelalawan Regency Manpower Office by 34.3%. While the remaining 65.7% describes other independent variables that were not observed in this study. Recommendations that can be submitted are expected to agencies to pay attention to the results achieved because they are not in accordance with the targets or standards that have been set.